Silsesquioxane-based inorganic-organic hybrid material, self-healing composition, self-healing molded article, and self-healing film, and method for producing silsesquioxane-based inorganic-organic hybrid material
Patent Information
- Application Number
- JP2026051607
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-28
- Filing Date
- 2026-03-26
- Publication Date
- 2026-10-13
AI Technical Summary
【0020】 本発明のシルセスキオキサン系無機有機ハイブリッド材は、硬度とヤング率が高く、透明性に優れ、高い自己修復能を有する新規な無機有機ハイブリッド材となる。
Smart Images

Figure 2026165085000008 
Figure 2026165085000009 
Figure 2026165085000010
Abstract
Description
[Technical Field]
[0001] The present invention relates to a silsesquioxane-based inorganic-organic hybrid material, a self-healing composition, a self-healing molded article, and a self-healing film, as well as a method for producing a silsesquioxane-based inorganic-organic hybrid material. [Background technology]
[0002] Self-healing materials are attracting attention as a technology that can contribute to resource and energy conservation through improved safety and product durability, as well as to achieving the Sustainable Development Goals (SDGs).
[0003] Self-healing materials have been reported that include intrinsic self-healing materials that utilize the rearrangement of bonds that make up polymer materials, non-autonomous self-healing materials that require external stimuli such as heat or light for repair, and autonomous self-healing materials that do not require external stimuli (see Patent Documents 1-5).
[0004] However, all of these self-healing materials, from the perspective of repairability, use soft polymer materials as their main component, and are insufficient in terms of hardness and mechanical properties.
[0005] Non-Patent Document 1 discloses a self-healing material possessing hardness and mechanical properties, in which an imidazole-zinc coordination bond is formed on the surface of silsesquioxane nanoparticles through ligand exchange between imidazole and zinc ions on the surface of the silsesquioxane nanoparticles. The material described in Non-Patent Document 1 is a self-healing material with a high Young's modulus.
[0006] However, the self-healing material described in Non-Patent Document 1 had low transparency and its mechanical properties were still insufficient.
[0007] Patent document 6 describes a self-healing organic-inorganic hybrid material that includes modified zirconium oxide particles or modified silica particles surface-modified with a functional group having an imidazole group at its terminus, and positively charged zinc, utilizing the ligand exchange action of zinc ions.
[0008] The self-healing material described in Patent Document 6 is a material with high hardness and Young's modulus. However, its transparency was not yet satisfactory.
[0009] Non-patent document 2 reports on various self-healing materials using silsesquioxane. However, the materials described in non-patent document 2 are mainly composed of polymer materials, and silsesquioxane is included as a modifier or additive.
[0010] Therefore, the self-healing material described in Non-Patent Document 2 did not sufficiently improve the properties due to the inorganic material silsesquioxane, and as a result, its mechanical properties were still unsatisfactory. [Prior art documents] [Patent Documents]
[0011] [Patent Document 1] Japanese Patent Publication No. 2021-107490 [Patent Document 2] Japanese Patent Publication No. 2020-015827 [Patent Document 3] Japanese Patent Publication No. 2023-079191 [Patent Document 4] Japanese Patent Publication No. 2024-138827 [Patent Document 5] Japanese Patent Publication No. 2023-545845 [Patent Document 6] Japanese Patent Publication No. 2023-148887 [Patent Document 7] Patent No. 5184082 [Non-patent literature]
[0012] [Non-Patent Document 1] Yusuke Sasaki, et al., “Self-healing hybrids fabricated by metal complexation with imidazole-containing silsesquioxane nanoparticles”, Materials Chemistry Frontiers, 4, 2655-2664 (2020) [Non-Patent Document 2] Maria Nowacka, et al., “Self-Healing Silsesquioxane-Based Materials”, Polymers, 14, 1869 (2022) [Non-Patent Document 3] Hideharu Mori, et al., “Intelligent colloidal hybrids via reversible pH-induced complexation of polyelectrolyte and silica nanoparticles, J. Am. Chem. Soc., 125, 3712-3713 (2003)”, J. Am. Chem. Soc., 125, 3712-3713 (2003) [Non-Patent Document 4] Hideharu Mori, et al., “Synthesis and characterization of water-soluble silsesquioxane-based nanoparticles by hydrolytic condensation of triethoxysilane derived from 2-hydroxyethyl acrylate”, Langmuir, 23, 9014-9023 (2007) [Non-Patent Document 5] Hideharu Mori, et al., “Synthesis and characterization of water-soluble SiO1.5 / TiO2 hybrid nanoparticles by hydrolytic co-condensation of triethoxysilane containing hydroxyl groups”, Materials Chemistry and Physics, 115, 287-295 (2009) [Overview of the project] [Problems that the invention aims to solve]
[0013] As described above, it has been difficult to achieve high hardness in resin compositions primarily composed of polymer materials as self-healing materials.
[0014] Furthermore, in compositions combining polymer materials having specific functional groups with inorganic materials, it is difficult to improve hardness due to the small interaction between the inorganic and polymer materials. When the filling density of the inorganic material was increased to improve hardness, the scratch resistance of the composition tended to decrease.
[0015] Furthermore, while organic-inorganic hybrid materials, such as silsesquioxane nanoparticles surface-modified with functional groups containing imidazole groups (Non-Patent Literature 1), and modified zirconium oxide particles or modified silica particles (Patent Literature 6) that exhibit ligand exchange with zinc ions, are materials that possess high Young's modulus while also providing self-healing properties, it has been difficult to achieve high transparency.
[0016] The present invention has been made in view of the above background, and aims to provide a novel inorganic-organic hybrid material, a self-healing composition, a self-healing molded article, and a self-healing film, as well as a method for producing an inorganic-organic hybrid material, which have high hardness and Young's modulus, excellent transparency, and high self-healing ability. [Means for solving the problem]
[0017] The inventors diligently conducted research to solve the above problems. As a result, they developed a particle consisting of a T unit in which one organic component and three oxygen atoms are bonded to a silicon atom (constituent unit: RSiO 1.5 By utilizing silsesquioxane nanoparticles, which are silsesquioxane-based inorganic-organic hybrid materials having boronic acid ester bonds, formed by the reaction of silsesquioxane-based particles having multiple hydroxyl groups on their outermost surface with a polyfunctional compound having at least one -B(OH)2 atomic group, we have found that this material can be a self-healing material having a reversible network structure due to the boronic acid ester bonds, and that the above-mentioned problems can be solved, thus completing the present invention.
[0018] In other words, the present invention includes the following embodiments.
[0019] [1] A boronic acid ester bond formed by reacting a silsesquioxane compound having multiple hydroxyl groups with a compound having at least one -B(OH)2 atomic group, The ratio of the hydroxyl group to the -B(OH)2 atomic group is in the range of 0.01 to less than 0.5 -B(OH)2 atomic groups per hydroxyl group. Silsesquioxane-based inorganic-organic hybrid material. [2] The silsesquioxane-based inorganic-organic hybrid material according to embodiment [1], wherein the boronic acid ester bond undergoes a reversible reaction, thereby having a reversible network structure. [3] The silsesquioxane-based inorganic-organic hybrid material according to embodiment [1], wherein the silsesquioxane-based compound is represented by the following chemical formula (1) and is surface-modified with the functional group having a hydroxyl group. (R 1 SiO 1.5 ) n (1) (In chemical formula (1), R 1(These may be the same or different hydrocarbon groups, having 1 to 4 hydroxyl groups and containing at least one selected from the group consisting of a tertiary amino group, an ester bond, and a thioether bond, where n is an integer from 3 to 30.) [4] The silsesquioxane-based inorganic-organic hybrid material according to embodiment [1], wherein the silsesquioxane-based compound is a particle with an average primary particle diameter of 1 nm to 20 nm. [5] The silsesquioxane-based inorganic-organic hybrid material according to embodiment [1], wherein the silsesquioxane-based compound is a composite with silica or titanium oxide. [6] The polyfunctional compound having at least one -B(OH)2 atomic group has a functional group that reacts with a hydroxyl group, according to embodiment [1], the silsesquioxane-based inorganic-organic hybrid material. [7] The silsesquioxane-based inorganic-organic hybrid material according to embodiment [1], wherein the polyfunctional compound having at least one -B(OH)2 atomic group is a compound obtained by substituting one of the four ethoxy groups of tetraoxysilane with an alkyl group having 12 or fewer carbon atoms. [8] The silsesquioxane-based inorganic-organic hybrid material according to embodiment [7], wherein the alkoxy group chain of a compound obtained by substituting one of the four ethoxy groups of the tetraalkoxysilane and / or the tetraoxysilane with an alkyl group having 12 or fewer carbon atoms contains at least one of an epoxy group, a thiol group, a (meth)acrylate group, and an ether group. [9] A self-healing composition comprising a silsesquioxane-based inorganic-organic hybrid material according to any one embodiment of [1] to [8].
[10] A self-healing molded article comprising a silsesquioxane-based inorganic-organic hybrid material according to any one of embodiments [1] to [8].
[11] A self-healing film comprising a silsesquioxane-based inorganic-organic hybrid material according to any one of embodiments [1] to [8].
[12] A method for producing a silsesquioxane-based inorganic-organic hybrid material, comprising reacting a silsesquioxane-based compound having multiple hydroxyl groups with a polyfunctional compound having at least one -B(OH)2 atomic group to form a boronic acid ester bond.
[13] The method for producing a silsesquioxane-based inorganic-organic hybrid material according to embodiment
[12] , wherein the silsesquioxane-based compound is a composite with silica or titanium oxide.
[14] The method for producing a silsesquioxane-based inorganic-organic hybrid material according to embodiment
[12] or
[13] , wherein the polyfunctional compound having at least one -B(OH)2 atomic group has a functional group that reacts with a hydroxyl group. [Effects of the Invention]
[0020] The silsesquioxane-based inorganic-organic hybrid material of the present invention is a novel inorganic-organic hybrid material that has high hardness and Young's modulus, excellent transparency, and high self-healing ability.
[0021] The silsesquioxane-based inorganic-organic hybrid material of the present invention has multiple boronic acid ester bonds. Since boronic acid ester bonds have a reversible structure, the silsesquioxane-based inorganic-organic hybrid material of the present invention becomes a self-healing material having a reversible network structure.
[0022] Furthermore, boronic acid ester bonds exhibit excellent thermal stability, and the reversible reaction between borate bonds is rapid, allowing them to be formed at room temperature without a catalyst from the -B(OH)2 atomic group and hydroxyl groups. Therefore, if a boronic acid ester bond is broken due to minute scratches or defects, it can be quickly reformed at room temperature using the hydroxyl groups present in the silsesquioxane-based compound and the polyfunctional compound having the -B(OH)2 atomic group. As a result, the silsesquioxane-based inorganic-organic hybrid material of the present invention exhibits high self-healing properties.
[0023] Furthermore, the silsesquioxane-based inorganic-organic hybrid material of the present invention possesses high hardness due to the structural portion of the silsesquioxane-based compound, which is an inorganic substance.
[0024] Furthermore, if the silsesquioxane compound is in the form of particles and has a small average particle size, the crosslinking density can be further improved, resulting in a further increase in hardness and Young's modulus.
[0025] Furthermore, the silsesquioxane-based inorganic-organic hybrid material of the present invention is composed mainly of carbon, oxygen, silicon, boron, and a small amount of nitrogen, and therefore has high transparency. [Brief explanation of the drawing]
[0026] [Figure 1] This is a conceptual diagram of a silsesquioxane-based inorganic-organic hybrid material, which is one embodiment of the present invention. [Figure 2] This is the 1H-NMR spectrum of (Gly-SiO1.5)n, a silsesquioxane compound containing Gly-TES and a hydroxyl group, prepared in Example 1. [Figure 3] These are the FT-IR spectra of (Gly-SiO1.5)n, a silsesquioxane compound containing a hydroxyl group prepared in Example 1, and the silsesquioxane / silica composite (Gly-SiO1.5 / SiO2) prepared in Example 7. [Figure 4] This is the stress-strain curve (SS curve) of (Gly-SiO1.5)n-PDBA, a silsesquioxane-based inorganic-organic hybrid material prepared in Examples 1-3. [Figure 5] These are the stress-strain curves (SS curves) of (Gly-SiO1.5)n-BTBA, a silsesquioxane-based inorganic-organic hybrid material prepared in Examples 4-6. [Figure 6] This is the evaluation result of the self-healing of (Gly-SiO1.5)n-PDBA, a silsesquioxane-based inorganic-organic hybrid material prepared in Example 3. [Figure 7]This is the evaluation result of the self-healing of (Gly-SiO1.5)n-BTBA, a silsesquioxane-based inorganic-organic hybrid material prepared in Example 4. [Figure 8] This is the result of evaluating the transparency of (Gly-SiO1.5)n-PDBA, a silsesquioxane-based inorganic-organic hybrid material prepared in Example 2. [Figure 9] This is the result of evaluating the transparency of (Gly-SiO1.5 / SiO2)-PDBA, a silsesquioxane-based inorganic-organic hybrid material prepared in Example 7. [Figure 10] These are the stress-strain curves (SS curves) of (Gly-SiO1.5 / SiO2)-PDBA, which are silsesquioxane-based inorganic-organic hybrid materials prepared in Examples 1, 7, and 8. [Figure 11] This is the evaluation result of the self-healing properties of (Gly-SiO1.5 / SiO2)-PDBA, a silsesquioxane-based inorganic-organic hybrid material prepared in Example 7. [Figure 12] These are the stress-strain curves (SS curves) of (Gly-SiO1.5)n-PDBA-ZnCl2, which are silsesquioxane-based inorganic-organic hybrid materials prepared in Examples 2, 3, 9, and 10. [Figure 13] These are the stress-strain curves (SS curves) of (Gly-SiO1.5)n-BA and (Gly-SiO1.5 / SiO2)-BA, which are silsesquioxane-based inorganic-organic hybrid materials prepared in Examples 11-13. [Figure 14] This is the stress-strain curve (SS curve) of (Gly-SiO1.5 / Hex)n-BA, a silsesquioxane-based inorganic-organic hybrid material fabricated in Example 14. [Figure 15] This is the stress-strain curve (SS curve) of (Gly-SiO1.5 / Hex / SiO2)n-BA, a silsesquioxane-based inorganic-organic hybrid material fabricated in Example 15. [Modes for carrying out the invention]
[0027] The present invention will now be described in detail with reference to the drawings. ≪Silsesquioxane-based inorganic-organic hybrid material≫ The silsesquioxane-based inorganic-organic hybrid material of the present invention has multiple boronic acid ester bonds formed by reacting the hydroxyl groups of a silsesquioxane-based compound having multiple hydroxyl groups with the -B(OH)2 atomic group of a polyfunctional compound having at least one -B(OH)2 atomic group.
[0028] Because boronic acid ester bonds are reversible structures that undergo reversible reactions, the silsesquioxane-based inorganic-organic hybrid material of the present invention is a self-healing material having a reversible network structure. Boronic acid ester bonds have excellent thermal stability, and the reversible reaction between borate bonds is fast. They can be generated from the -B(OH)2 atomic group and hydroxyl group at room temperature without a catalyst. Therefore, the silsesquioxane-based inorganic-organic hybrid material of the present invention rapidly self-heals even at room temperature. Accordingly, the silsesquioxane-based inorganic-organic hybrid material of the present invention has high self-healing properties.
[0029] Furthermore, the silsesquioxane-based inorganic-organic hybrid material of the present invention possesses high hardness and Young's modulus due to properties derived from the inorganic silsesquioxane compound. Moreover, because the constituent elements of the silsesquioxane-based inorganic-organic hybrid material of the present invention are mainly carbon, oxygen, silicon, boron, and a small amount of nitrogen, it exhibits excellent transparency.
[0030] The shape of the silsesquioxane-based inorganic-organic hybrid material of the present invention is not particularly limited and may be in the form of a powder or dispersed in a solvent.
[0031] Figure 1 shows a conceptual diagram of a silsesquioxane-based inorganic-organic hybrid material, which is one embodiment of the present invention. As shown in Figure 1, the silsesquioxane-based inorganic-organic hybrid material 30 contains a silsesquioxane-based compound 10 and a polyfunctional compound 20 having a -B(OH)2 atomic group as components. The surface of the silsesquioxane-based compound 10 has multiple hydroxyl groups 1 and is surface-modified with functional groups (organic components) having hydroxyl groups 1.
[0032] In the silsesquioxane-based inorganic-organic hybrid material 30, the hydroxyl groups 1 of the silsesquioxane-based compound 20, which have multiple hydroxyl groups 1, react with the B(OH)2 atomic group of the polyfunctional compound 20, which has a -B(OH)2 atomic group, to form a boronic acid ester bond.
[0033] As shown in Figure 1, the boronic acid ester bond is a reversible structure that undergoes reversible reactions, and the reversible reaction between borate bonds is rapid. The boronic acid ester bond has excellent thermal stability, and even if the bond is broken due to external factors, it can be regenerated at room temperature without a catalyst from the -B(OH)2 atomic group and the hydroxyl group. For this reason, the silsesquioxane-based inorganic-organic hybrid material of the present invention has high self-healing properties.
[0034] [Total content of organic components] In the silsesquioxane-based inorganic-organic hybrid material of the present invention, the total content of organic components, which is the sum of boronic acid ester bonds and functional groups (organic components) in the silsesquioxane-based compound, is preferably in the range of 10% by mass or more and 60% by mass or less of the total silsesquioxane-based inorganic-organic hybrid material.
[0035] If the total content of organic components is less than 10% by mass, boronic acid ester bonds may not be sufficiently formed, potentially resulting in insufficient self-healing properties. On the other hand, if the total content of organic components exceeds 60% by mass, the amount of inorganic components will be relatively low, potentially making it difficult to achieve sufficient hardness.
[0036] The total content of organic components in the silsesquioxane-based inorganic-organic hybrid material is calculated by the weight loss rate up to 650°C in thermogravimetric analysis (TGA) measurement under nitrogen, and may be 10 mass% or more, 15 mass% or more, or 20 mass% or more, and may be 60 mass% or less, 55 mass% or less, or 50 mass% or less, relative to the entire silsesquioxane-based inorganic-organic hybrid material.
[0037] <Silsesquioxane-based compound having a plurality of hydroxyl groups> The silsesquioxane-based compound having a plurality of hydroxyl groups, which is a raw material of the silsesquioxane-based inorganic-organic hybrid material of the present invention, has a plurality of hydroxyl groups on the surface of the compound. These hydroxyl groups react with the -B(OH)₂ atomic group of the polyfunctional compound having a -B(OH)₂ atomic group described later, thereby forming a plurality of boronic acid ester bonds, to give the silsesquioxane-based inorganic-organic hybrid material of the present invention.
[0038] It is preferable that the silsesquioxane-based compound having a plurality of hydroxyl groups, which is a raw material of the silsesquioxane-based inorganic-organic hybrid material of the present invention, is represented by the following chemical formula (1) and is surface-modified with a functional group having a hydroxyl group. (R 1 SiO 1.5 ) n (1) (In chemical formula (1), R 1 may be the same or different, each is a hydrocarbon group having 1 to 4 hydroxyl groups and containing at least one selected from the group consisting of a tertiary amino group, an ester bond, and a thioether bond, and n is an integer of 3 to 30.)
[0039] That is, the silsesquioxane-based compound having a plurality of hydroxyl groups is a compound composed of T units in which one organic component and three oxygen atoms are bonded to a silicon atom (structural unit: RSiO 1.5 ), the surface of which is modified with a functional group having a hydroxyl group (organic component), and which has a plurality of hydroxyl groups on the surface.
[0040] The shape of silsesquioxane compounds having multiple hydroxyl groups is not particularly limited. Examples of silsesquioxane compounds include spherical, elliptical, and polygonal prismatic particles.
[0041] In the present invention, the silsesquioxane compound having multiple hydroxyl groups is preferably a particle with an average primary particle diameter of 1 nm to 20 nm. However, when the silsesquioxane compound is in the form of particles, its shape is not particularly limited, and it may be, for example, a powder or a paste-like viscous body.
[0042] Silsesquioxane compounds having multiple hydroxyl groups with an average primary particle diameter within this range have fine particles, allowing for the introduction of dense boronic acid ester bonds into silsesquioxane-based inorganic-organic hybrid materials through reaction with polyfunctional compounds containing -B(OH)2 atomic groups. As a result, the crosslinking density of the silsesquioxane-based inorganic-organic hybrid material increases, further improving the hardness and Young's modulus of molded products obtained from it.
[0043] When the average primary particle diameter of a silsesquioxane-based compound having multiple hydroxyl groups exceeds 20 nm, the specific surface area of the silsesquioxane-based compound particles decreases, and the amount of hydroxyl groups, which are organic components, present on the particle surface decreases. This can lead to a decrease in the crosslinking density of the silsesquioxane-based inorganic-organic hybrid material, potentially preventing the molded product obtained from the silsesquioxane-based inorganic-organic hybrid material from achieving sufficient hardness.
[0044] The average primary particle size of a silsesquioxane compound having multiple hydroxyl groups may be 1 nm or more, or 1.5 nm or more, and may be 20 nm or less, 15 nm or less, or 15 nm or less.
[0045] In this specification, "average primary particle size" refers to the height of uniform, monodisperse spherical particles in an atomic force microscope (AFM) image obtained by measuring a thin film prepared by depositing a solution of a silsesquioxane compound on a mica substrate using the tapping mode of an atomic force microscope (5500 Scanning Probe Microscope, manufactured by Agilent Technologies).
[0046] The silsesquioxane-based compound having multiple hydroxyl groups, which serves as a material for the silsesquioxane-based inorganic-organic hybrid material of the present invention, may be a composite with silica (SiO2) or titanium dioxide (TiO2). That is, the silsesquioxane-based compound that serves as a material for the silsesquioxane-based inorganic-organic hybrid material of the present invention may be a silsesquioxane / silica composite (RSiO2). 1.5 (SiO2), or silsesquioxane / titanium dioxide (RSiO2) 1.5 A TiO2 complex may also be used.
[0047] In the present invention, the silsesquioxane-based compound used as the material for the silsesquioxane-based inorganic-organic hybrid material is a composite with silica (SiO2) or titanium dioxide (TiO2), which increases the inorganic component content and improves hardness, mechanical properties, and transparency.
[0048] <Method for producing silsesquioxane compounds having multiple hydroxyl groups> The silsesquioxane-based compounds having multiple hydroxyl groups, which serve as materials for the silsesquioxane-based inorganic-organic hybrid material of the present invention, can be prepared, for example, by the methods described in Non-Patent Document 3 and Patent Document 7.
[0049] Specifically, as shown in (a) below, silsesquioxane compounds having multiple hydroxyl groups can be synthesized by using 3-(aminopropyl)triethoxysilane (1 equivalent) and glycidol (2 equivalents) as starting materials, reacting the trialkoxysilane intermediate obtained by the addition reaction in methanol in the presence of hydrogen fluoride at room temperature for 2 hours, and then removing the solvent under reduced pressure.
[0050] [ka]
[0051] As materials for synthesizing silsesquioxane compounds having multiple hydroxyl groups, epoxy compounds such as glycidol, as well as acrylate derivatives having hydroxyl groups, can also be used. The preparation of silsesquioxane compounds having hydroxyl groups using acrylate derivatives as raw materials can be carried out, for example, according to the method described in Non-Patent Document 4.
[0052] Specifically, as shown in (b) above, 3-(aminopropyl)triethoxysilane (1 equivalent) and 2-hydroxyethyl acrylate (2 equivalents) are used as raw materials, and a trialkoxysilane intermediate is synthesized by the Michael addition reaction. By carrying out the hydrolysis and condensation reaction of this intermediate under acidic conditions, a silsesquioxane compound having multiple hydroxyl groups can be synthesized.
[0053] For the synthesis of silsesquioxane compounds, alkoxysilane compounds that have functional groups that can ultimately be converted to hydroxyl groups can be used as raw materials. Examples of functional groups that can ultimately be converted to hydroxyl groups include amino groups, as well as epoxy groups, acrylate groups, methacrylate groups, mercapto groups, and vinyl groups.
[0054] A method for converting functional groups to hydroxyl groups can be carried out, for example, according to the description in Non-Patent Document 1. Specifically, as shown below, for example, a hydrolysis-condensation reaction with an epoxy group-containing alkoxysilane compound can be carried out under acidic conditions to synthesize a silsesquioxane compound having multiple epoxy groups, and a silsesquioxane-based compound having multiple hydroxyl groups can be synthesized by a ring-opening reaction between the epoxy groups and a thiol compound.
[0055] [ka]
[0056] (Method for producing a silica composite) A silsesquioxane / silica complex (RSiO2) is a composite of a silsesquioxane compound and silica (SiO2). 1.5 For example, SiO2 can be produced according to the method described in Non-Patent Document 4.
[0057] Specifically, it is prepared using a co-condensation reaction between a trifunctional trialkoxysilane compound "R-Si(OR')3" containing an organic moiety and a tetrafunctional tetraalkoxysilane "Si(OR'')4".
[0058] For example, by hydrolysis and condensation of a trialkoxysilane intermediate obtained by the addition reaction of 3-(aminopropyl)triethoxysilane and glycidol with tetraethoxysilane, a silsesquioxane / silica complex (RSiO2) with different inorganic components can be obtained. 1.5 It is possible to synthesize (SiO2).
[0059] For example, the alkoxy groups (OR' and OR'') of the trialkoxysilane compound "R-Si(OR')3" and the tetrafunctional tetraalkoxysilane "Si(OR'')4" can be methoxy groups, ethoxy groups, propoxy groups, isopropoxy groups, butoxy groups, etc.
[0060] Furthermore, the alkoxy group chain may contain an alkyl group having 12 or fewer carbon atoms, such as a hexyl group. By introducing an alkyl group having 12 or fewer carbon atoms, the hydrophobicity of the polyfunctional compound can be improved.
[0061] Furthermore, the alkoxy group chain may contain epoxy groups, thiol groups, (meth)acrylate groups, or ether groups. In particular, the inclusion of epoxy groups can improve film formation when the silsesquioxane-based inorganic-organic hybrid material of the present invention is used to form a self-healing film.
[0062] In this cocondensation system, the reaction can be carried out under conditions where the molar ratio of the initial composition is R-Si(OR')3:Si(OR'')4 = 90:10 to 10:90, thereby enabling the production of silsesquioxane / silica composites (RSiO) with different inorganic component compositions, solubility, and thermal stability. 1.5 You can obtain ( / SiO2).
[0063] (Method for producing a composite with titanium dioxide) Silsesquioxane / titanium dioxide (RSiO) is a composite of a silsesquioxane compound and titanium dioxide (TiO2). 1.5 The / TiO2) composite can be prepared, for example, according to the method described in Non-Patent Document 5.
[0064] Specifically, it is prepared using a co-condensation reaction between a trifunctional trialkoxysilane compound "R-Si(OR')3" containing an organic moiety and a tetrafunctional tetraalkoxytitanium "Ti(OR'')4".
[0065] For example, by hydrolysis and condensation of a trialkoxysilane intermediate obtained by the addition reaction of 3-(aminopropyl)triethoxysilane and 2-hydroxyethyl acrylate with tetraisopropoxytitanium, a silsesquioxane / titanium dioxide composite (RSiO) with different inorganic components can be obtained. 1.5 It is possible to synthesize TiO2.
[0066] For example, the alkoxy groups (OR' and OR'') of the trialkoxysilane compound "R-Si(OR')3" and the tetrafunctional tetraalkoxytitanium "Ti(OR'')4" can be methoxy groups, ethoxy groups, propoxy groups, isopropoxy groups, butoxy groups, etc.
[0067] In this cocondensation system, the reaction can be carried out under conditions where the molar ratio of the starting composition is R-Si(OR')3:Ti(OR'')4 = 90:10 to 10:90, thereby enabling the formation of silsesquioxane / titanium oxide composites (RSiO) with different inorganic component compositions, solubility, and thermal stability. 1.5You can obtain (TiO2).
[0068] <Polyfunctional compounds having at least one -B(OH)2 atomic group> The polyfunctional compound having at least one -B(OH)2 atomic group, which serves as a material for the silsesquioxane-based inorganic-organic hybrid material of the present invention, is a compound having one or more -B(OH)2 atomic groups per molecule.
[0069] The -B(OH)2 group of a polyfunctional compound having at least one -B(OH)2 group reacts with the hydroxyl group of the silsesquioxane compound having the multiple hydroxyl groups described above to form a boronic acid ester bond.
[0070] A polyfunctional compound having at least one -B(OH)2 atomic group has at least two functional groups. That is, a polyfunctional compound having at least one -B(OH)2 atomic group may also be a compound having at least two -B(OH)2 atomic groups, or a compound having at least one -B(OH)2 atomic group and at least one functional group different from the -B(OH)2 atomic group.
[0071] The silsesquioxane-based inorganic-organic hybrid material of the present invention has a network structure if the polyfunctional compound having at least one -B(OH)2 atomic group is a polyfunctional compound having two or more -B(OH)2 atomic groups in one molecule, or a compound having at least one -B(OH)2 atomic group in one molecule and at least one functional group different from the -B(OH)2 atomic group.
[0072] The functional group is not particularly limited to those other than the -B(OH)2 atomic group. In particular, any functional group that reacts with a hydroxyl group is preferred because it can react with the hydroxyl groups of a silsesquioxane compound having multiple hydroxyl groups to form bonds, thereby contributing to the network structure of the silsesquioxane-based inorganic-organic hybrid material of the present invention.
[0073] Examples of functional groups that react with hydroxyl groups include carboxyl groups, sulfonic acid groups, hydroxyl groups, silyl groups, hydroxysilyl groups, epoxy groups, isocyanate groups, and amino groups. Among these, hydroxyl groups are preferred because they do not increase the variety of elements constituting the silsesquioxane-based inorganic-organic hybrid material.
[0074] Examples of polyfunctional compounds having two or more -B(OH)2 atomic groups in one molecule include 1,4-phenyldiboronic acid (DPBA), benzene-1,3,5-triylboronic acid (BTBA), and their derivatives.
[0075] Examples of compounds having at least one -B(OH)2 atomic group and at least one functional group different from the -B(OH)2 atomic group in one molecule include boric acid (BA).
[0076] ≪Method for manufacturing silsesquioxane-based inorganic-organic hybrid materials≫ The method for producing silsesquioxane-based inorganic-organic hybrid materials is not particularly limited. Silsesquioxane-based inorganic-organic hybrid materials can be produced by reacting the hydroxyl groups of a silsesquioxane-based compound having multiple hydroxyl groups with the -B(OH)2 atomic group of a polyfunctional compound having at least one -B(OH)2 atomic group to form a boronic acid ester bond.
[0077] Furthermore, in the method for producing silsesquioxane-based inorganic-organic hybrid materials, the silsesquioxane-based compound having multiple hydroxyl groups is the silsesquioxane / silica composite (RSiO) described above. 1.5 (SiO2), or silsesquioxane / titanium dioxide (RSiO2) 1.5 A TiO2 complex may also be used.
[0078] For example, first, a silsesquioxane compound having multiple hydroxyl groups is dispersed in a solvent to obtain a dispersion. Next, while stirring the obtained dispersion, a solution of 1,4-phenyldiboronic acid (a polyfunctional compound having two -B(OH)2 atomic groups) is added and mixed to prepare a liquid composition. Subsequently, by removing the solvent from the obtained liquid composition, a silsesquioxane-based inorganic-organic hybrid material can be prepared.
[0079] Solvents used in the production of silsesquioxane-based inorganic-organic hybrid materials include, for example, water, organic solvents, and mixtures containing water and organic solvents.
[0080] Examples of organic solvents include lower aliphatic ethers having 1 to 5 carbon atoms, lower alcohols having 1 to 5 carbon atoms, lower aliphatic ketones having 1 to 5 carbon atoms, and aprotic polar solvents.
[0081] Examples of lower ethers include tetrahydrofuran, 1,4-dioxane, and diethyl ether. Examples of lower alcohols include methanol, ethanol, 1-propanol, 2-propanol, ethylene glycol, glycerin, and propylene glycol 1-monomethyl ether. Examples of lower aliphatic ketones include acetone and methyl ethyl ketone. Examples of aprotic polar solvents include acetonitrile, N,N-dimethylformamide, and dimethyl sulfoxide. As for the mixture containing water and organic solvent, for example, a mixture in the mass ratio range of 9:1 to 1:9 (organic solvent:water) is preferred.
[0082] The method for removing the solvent is not particularly limited, and known methods can be employed. One example of a method for removing the solvent is vacuum drying.
[0083] (Ratio of hydroxyl group to -B(OH)2 atomic group) In the silsesquioxane-based inorganic-organic hybrid material of the present invention, a boronic acid ester bond is formed by the reaction of a hydroxyl group of a silsesquioxane-based compound having multiple hydroxyl groups with a -B(OH)2 atomic group of a polyfunctional compound having at least one -B(OH)2 atomic group.
[0084] In silsesquioxane-based inorganic-organic hybrid materials, the ratio of hydroxyl groups to -B(OH)2 atomic groups in the silsesquioxane compound is in the range of 0.01 to less than 0.5 -B(OH)2 atomic groups per hydroxyl group, and preferably 0.05 to 0.3 -B(OH)2 atomic groups per hydroxyl group.
[0085] When multiple silsesquioxane-based compounds are bonded to a polyfunctional compound having at least one -B(OH)2 atomic group, molded articles obtained from silsesquioxane-based inorganic-organic hybrid materials exhibit high hardness and Young's modulus. Furthermore, in the silsesquioxane-based inorganic-organic hybrid material of the present invention, if there are 0.5 or more -B(OH)2 atomic groups per hydroxyl group, it will not deform even with hot pressing at 120°C, for example, which presents problems with processability.
[0086] Furthermore, because multiple silsesquioxane compounds are bonded to a polyfunctional compound having at least one -B(OH)2 atomic group, when the boronic acid ester moiety is cleaved, the polyfunctional compound having at least one -B(OH)2 atomic group can rapidly form bonds not only with the hydroxyl group on the original silsesquioxane compound, but also with other nearby hydroxyl groups and hydroxyl groups on other silsesquioxane compounds. As a result, the cleaved boronic acid ester bond can be quickly reconstructed, and molded articles made from the silsesquioxane-based inorganic-organic hybrid material of the present invention can be repaired quickly in the event of minor scratches or defects.
[0087] ≪Self-healing composition≫ The self-healing composition of the present invention is a composition comprising the silsesquioxane-based inorganic-organic hybrid material of the present invention described above.
[0088] The silsesquioxane-based inorganic-organic hybrid material of the present invention can be used as a self-healing material on its own, but it can also be used as a composition by incorporating other components as needed.
[0089] Other components are not particularly limited and can be added within a range that does not impair the effects of the silsesquioxane-based inorganic-organic hybrid material of the present invention. Examples of other components include other resins, additives, and solvents.
[0090] For example, if the silsesquioxane-based inorganic-organic hybrid material of the present invention has a tertiary amino group in the chemical structure of the organic component, compounds or additives that have a configuration that forms a non-covalent bond with the amine moiety can be incorporated, to the extent that they do not impede the effects of the present invention.
[0091] Examples of materials that form non-covalent bonds with the amine moiety include metal salts that coordinate with the tertiary amino group, such as zinc chloride, bis(trifluoromethanesulfonic acid)zinc, and bis(trifluoromethanesulfonyliimide)zinc.
[0092] Bonds that form non-covalent bonds with the amine moiety are reversible bonds, similar to boronic acid ester bonds. Therefore, silsesquioxane-based inorganic-organic hybrid materials that have amine-metal coordination bonds in addition to boronic acid ester bonds can improve elastic modulus and hardness because the two reversible non-covalent bonds work synergistically.
[0093] In the case of a liquid composition, for example, it can be prepared by dispersing the silsesquioxane-based inorganic-organic hybrid material of the present invention in a solvent. Alternatively, by leaving the solvent used in the manufacturing process of the silsesquioxane-based inorganic-organic hybrid material of the present invention as is, a self-healing composition can be obtained in which the silsesquioxane-based inorganic-organic hybrid material is uniformly dispersed in the solvent or dispersed in a colorless, transparent colloidal solution.
[0094] ≪Self-healing molded body≫ The self-healing molded article of the present invention is a molded article containing the silsesquioxane-based inorganic-organic hybrid material of the present invention as described above.
[0095] The method for producing a self-healing molded article containing a silsesquioxane-based inorganic-organic hybrid material is not particularly limited, and known methods can be applied. After producing a silsesquioxane-based inorganic-organic hybrid material or a composition thereof, the molded article may be produced using the obtained silsesquioxane-based inorganic-organic hybrid material or composition thereof, or the molded article may be produced continuously from the production process of the silsesquioxane-based inorganic-organic hybrid material.
[0096] One method for continuously producing molded articles from the manufacturing process of silsesquioxane-based inorganic-organic hybrid materials is to add a solution of a polyfunctional compound having at least one -B(OH)2 atomic group to a dispersion of several silsesquioxane-based compounds, and optionally add and mix additives that form tertiary amino groups, ester bonds, and thioether bonds with non-covalent bonds (hydrogen bonds, metal coordination bonds, etc.) to prepare a liquid composition. Subsequently, after removing some of the solvent from the obtained liquid composition, the mixture is poured into a mold and dried to obtain a molded article.
[0097] Furthermore, a method for producing a molded article using the obtained silsesquioxane-based inorganic-organic hybrid material or composition thereof is, for example, a pressure molding method. In the pressure molding method, for example, a molded article is obtained by filling a mold with powder of the silsesquioxane-based inorganic-organic hybrid material or composition thereof and heating it under pressure.
[0098] In the self-healing molded article of the present invention, it is preferable that the silsesquioxane-based compound within the molded article is uniformly dispersed and does not form aggregates, in order to achieve faster self-healing.
[0099] ≪Self-healing membrane≫ The self-healing film of the present invention is a film containing the silsesquioxane-based inorganic-organic hybrid material of the present invention described above.
[0100] The thickness of the self-healing film of the present invention is, for example, within the range of 1 μm to 5000 μm.
[0101] The method for producing a self-healing film containing a silsesquioxane-based inorganic-organic hybrid material is not particularly limited, and known methods can be applied. The self-healing film of the present invention can be formed, for example, from a dispersion containing the silsesquioxane-based inorganic-organic hybrid material of the present invention as described above.
[0102] More specifically, a self-healing film can be formed by applying a liquid composition containing a silsesquioxane-based inorganic-organic hybrid material to the surface of an object on which a coating film is to be formed, creating a coating layer, and then heating the coating layer to remove the solvent that constituted the liquid composition.
[0103] In the self-healing membrane of the present invention, it is preferable that the silsesquioxane-based compounds within the membrane are uniformly dispersed and do not form aggregates, in order to achieve faster self-healing.
[0104] Applications of silsesquioxane-based inorganic-organic hybrid materials The applications of the silsesquioxane-based inorganic-organic hybrid material of the present invention are not particularly limited and can be applied to a variety of uses. [Examples]
[0105] The present invention will be described in more detail below based on examples, but the present invention is not limited in any way by the following examples.
[0106] <Measuring equipment> The instruments used for identifying the compounds in the examples and comparative examples are as follows: (1) 1 H nuclear magnetic resonance method ( 1HNMR) JEOL Ltd., 400MHz, JNM-ECX400 (2) FT-IR FT-710, manufactured by Horiba, Ltd.
[0107] <Example 1> [Production of silsesquioxane compounds containing hydroxyl groups] Silsesquioxane compounds containing hydroxyl groups were prepared using the following synthetic routes. The synthetic schemes for each route are shown below.
[0108] [ka]
[0109] Gly-TES was synthesized by adding 1.48 g (20.0 mmol) of glycidol and 2.33 mL (10.0 mmol) of 3-(aminopropyl)triethoxysilane to a nitrogen-purged, two-necked round-bottom flask under ice cooling, and reacting at room temperature for 1 hour.
[0110] Next, 5.40 mL of methanol was added, and while stirring, 0.328 mL of 3.2 wt% HFaq. was slowly added dropwise, and the mixture was reacted at room temperature for 2 hours. After the reaction, the solvent and other substances were removed under reduced pressure using an evaporator and then a vacuum dryer, yielding a silsesquioxane compound containing a hydroxyl group (Gly-SiO 1.5 ) n A colorless, transparent solid was obtained.
[0111] Figure 2 shows Gly-TES and the resulting silsesquioxane compound having a hydroxyl group (Gly-SiO 1.5 ) n of 1 The 1H NMR spectrum is shown. Figure 3 also shows the obtained silsesquioxane compound containing a hydroxyl group (Gly-SiO 1.5 ) n The FT-IR spectrum is shown.
[0112] [Manufacturing of silsesquioxane-based inorganic-organic hybrid materials] Silsesquioxane-based inorganic-organic hybrid materials were prepared using the following synthesis route.
[0113] [ka]
[0114] The above-mentioned silsesquioxane compound having a hydroxyl group is (Gly-SiO 1.5 ) n Then, by reacting it with 1,4-phenylenediboronic acid (PDBA), a silsesquioxane-based inorganic-organic hybrid material (Gly-SiO 1.5 ) n - PDBA obtained.
[0115] In a round-bottom flask, a silsesquioxane compound (Gly-SiO 1.5 ) n 1.03 g (4.0 mmol) of [the compound] and 10 mL of distilled water were added to uniformly dissolve the silsesquioxane compound. Subsequently, a dispersion of 1,4-dioxane (4 mL) containing 0.133 g (0.4 mmol) of 1,4-phenylenediboronic acid (PDBA) was added dropwise, and the mixture was stirred at 30°C for 1 hour to form a silsesquioxane-based inorganic-organic hybrid material (Gly-SiO2). 1.5 ) n - PDBA obtained.
[0116] <Examples 2-3> In the production of silsesquioxane-based inorganic-organic hybrid materials, the silsesquioxane compound (Gly-SiO 1.5 ) n Except for changing the charging ratio with 1,4-phenylenediboronic acid (PDBA) as shown in Table 1, the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO) was prepared in the same manner as in Example 1. 1.5 ) n - PDBA obtained.
[0117] <Example 4> [Production of silsesquioxane compounds containing hydroxyl groups] In the same manner as in Example 1, a silsesquioxane compound having a hydroxyl group (Gly-SiO 1.5 ) n A colorless, transparent solid was obtained.
[0118] [Manufacturing of silsesquioxane-based inorganic-organic hybrid materials] The above-mentioned silsesquioxane compound having a hydroxyl group is (Gly-SiO 1.5 ) n This is reacted with the trifunctional benzene 1,3,5-triylboronic acid (BTBA) to produce a silsesquioxane-based inorganic-organic hybrid material (Gly-SiO 1.5 ) n -BTBA obtained.
[0119] In a round-bottom flask, a silsesquioxane compound (Gly-SiO 1.5 ) n 1.03 g (4.0 mmol) of [the compound] and 10 mL of distilled water were added to uniformly dissolve the silsesquioxane compound. Subsequently, a dispersion of 1,4-dioxane (4 mL) containing 0.0838 g (0.4 mmol) of benzene 1,3,5-triylboronic acid (BTBA) was added dropwise, and the mixture was stirred at 30°C for 1 hour to form a silsesquioxane-based inorganic-organic hybrid material (Gly-SiO2). 1.5 ) n -BTBA obtained.
[0120] <Examples 5-6> In the production of silsesquioxane-based inorganic-organic hybrid materials, the silsesquioxane compound (Gly-SiO 1.5 ) n Except for changing the charging ratio of benzene 1,3,5-triylboronic acid (BTBA) as shown in Table 1, the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO) was obtained in the same manner as in Example 4. 1.5 ) n -BTBA obtained.
[0121] <Comparative Example 1> [Production of silsesquioxane compounds containing hydroxyl groups] In the same manner as in Example 1, a silsesquioxane compound having a hydroxyl group (Gly-SiO 1.5 ) n A colorless, transparent solid was obtained.
[0122] [Manufacturing of silsesquioxane-based inorganic-organic hybrid materials] The above-mentioned silsesquioxane compound having a hydroxyl group is (Gly-SiO 1.5 ) n Equimolar amounts of 1,4-phenylenediboronic acid (PDBA) and the mixture were dissolved in DMF and reacted at room temperature for 2 hours. After the reaction, the solvent and other substances were removed under reduced pressure using an evaporator and then a vacuum dryer to obtain a colorless, transparent solid.
[0123] <Example 7> [Silsesquioxane / Silica composite (Gly-SiO 1.5 [Manufacturing of SiO2] The following synthetic route produces a silsesquioxane / silica complex (Gly-SiO 1.5 We prepared (SiO2). The synthesis schemes for each route are shown below.
[0124] [ka]
[0125] Gly-TES was synthesized in the same manner as in Example 1.
[0126] Next, 5.40 mL of methanol was added, and while stirring, 0.521 g (2.5 mmol) of tetraethoxysilane and 0.328 mL of 3.2 wt% HFaq. were slowly added dropwise, and the mixture was reacted at room temperature for 2 hours. After the reaction, the solvent was removed under reduced pressure, and the mixture was dried overnight at 40°C under reduced pressure to obtain the silsesquioxane / silica complex (Gly-SiO 1.5 A transparent solid was obtained with a SiO2 ratio of 8:2.
[0127] The resulting silsesquioxane / silica composite (Gly-SiO 1.5 Solubility tests were conducted on SiO2, and it was confirmed that it is soluble in highly polar solvents such as water, methanol, DMF, and DMSO.
[0128] Figure 3 shows the obtained silsesquioxane / silica composite (Gly-SiO 1.5 The FT-IR spectrum of the silsesquioxane / silica composite (Gly-SiO2) is shown. From the FT-IR spectrum shown in Figure 3, it can be seen that 1.5 It can be confirmed that the molecule (SiO2=8:2) is modified with a functional group containing a hydroxyl group.
[0129] [Manufacturing of silsesquioxane-based inorganic-organic hybrid materials] The silsesquioxane / silica composite having hydroxyl groups prepared as described above (Gly-SiO 1.5 (Gly-SiO2) is reacted with 1,4-phenylenediboronic acid (PDBA) to produce a silsesquioxane-based inorganic-organic hybrid material (Gly-SiO2) (SiO2 = 8:2). 1.5 / SiO2)-PDBA was obtained.
[0130] In a round-bottom flask, a silsesquioxane / silica composite (Gly-SiO 1.5 1.27 g (5.8 mmol) of (SiO2=8:2) and 10 mL of distilled water were added to uniformly dissolve the silsesquioxane / silica composite. Subsequently, a dispersion of 1,4-dioxane (4 mL) containing 0.1160 g (0.7 mmol) of 1,4-phenylenediboronic acid (PDBA) was added dropwise, and the mixture was stirred at room temperature for 1 hour to form a silsesquioxane-based inorganic-organic hybrid material (Gly-SiO2). 1.5 ( / SiO2) n - PDBA obtained.
[0131] <Example 8> In the production of silsesquioxane-based inorganic-organic hybrid materials, silsesquioxane / silica composite (Gly-SiO 1.5Except for changing the charging ratio of (SiO2 = 8:2) and 1,4-phenylenediboronic acid (PDBA) as shown in Table 1, the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO2) was constructed in the same manner as in Example 7. 1.5 ( / SiO2) n - PDBA obtained.
[0132] <Example 9> [Production of silsesquioxane compounds containing hydroxyl groups] In the same manner as in Example 1, a silsesquioxane compound having a hydroxyl group (Gly-SiO 1.5 ) n A colorless, transparent solid was obtained.
[0133] [Manufacturing of silsesquioxane-based inorganic-organic hybrid materials] The above-mentioned silsesquioxane compound having a hydroxyl group is (Gly-SiO 1.5 ) n The reaction with 1,4-phenylenediboronic acid (PDBA) was carried out in the presence of zinc chloride to produce a silsesquioxane-based inorganic-organic hybrid material (Gly-SiO 1.5 ) n -PDBA-ZnCl2 was obtained.
[0134] In a round-bottom flask, a silsesquioxane compound (Gly-SiO 1.5 ) n 1.03 g (4.0 mmol) of [component name] and 8 mL of distilled water were added to uniformly dissolve the silsesquioxane compound. Subsequently, a dispersion of 1,4-dioxane (4 mL) containing 0.116 g (0.7 mmol) of 1,4-phenylenediboronic acid (PDBA) was added dropwise. Next, a dispersion of ZnCl2 (0.136 g (1.0 mmol) in 8 mL of distilled water was added dropwise, and the mixture was stirred at room temperature for 8 hours to obtain a silsesquioxane-based inorganic-organic hybrid material (Gly-SiO2). 1.5 ) n -PDBA-ZnCl2 was obtained.
[0135] <Example 10> In the production of a silsesquioxane-based inorganic-organic hybrid material, the silsesquioxane-based compound (Gly-SiO 1.5 ) n and 1,4-phenylenediboronic acid (PDBA) were used in a charging ratio varied as shown in Table 1, and the procedure was carried out in the same manner as in Example 9 to obtain the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO 1.5 ) n -PDBA-ZnCl2.
[0136] <Example 11> A round-bottom flask was charged with 1.03 g (4.0 mmol) of the silsesquioxane-based compound (Gly-SiO 1.5 ) n and 10 mL of distilled water, and the silsesquioxane-based compound was uniformly dissolved. Subsequently, a dispersion of 0.0989 g (1.6 mmol) of boric acid (B(OH)3, BA) in 4 mL of methanol was added dropwise, and the mixture was stirred at room temperature for 1 hour to obtain the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO 1.5 ) n -BA.
[0137] <Example 12> The procedure was carried out in the same manner as in Example 10, except that the charging ratio of the silsesquioxane-based compound (Gly-SiO 1.5 ) n and boric acid (BA) was varied as shown in Table 1, to obtain the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO 1.5 ) n -BA.
[0138] <Example 13> A round-bottom flask was charged with 0.8668 g (4.0 mmol) of the silsesquioxane / silica composite (Gly-SiO 1.5 / SiO2 = 8:2) and 10 mL of distilled water, and the silsesquioxane / silica composite was uniformly dissolved. Subsequently, a dispersion of 0.0742 g (1.2 mmol) of boric acid (BA) in 4 mL of methanol was added dropwise, and the mixture was stirred at room temperature for 1 hour to obtain the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO 1.5( / SiO2) n -Received a BA.
[0139] <Example 14> [Silsesquioxane / Hexylsilsesquioxane complex (Gly-SiO 1.5 [Manufacturing of Hex] Gly-TES was synthesized in the same manner as in Example 1.
[0140] Next, 5.40 mL of methanol was added, and while stirring, 0.276 g (1.1 mmol) of hexyltriethoxysilane and 0.328 mL of 3.2 wt% HFaq. were slowly added dropwise, and the mixture was reacted at room temperature for 2 hours. After the reaction, the solvent was removed under reduced pressure, and the mixture was dried overnight at 40°C under reduced pressure to form a silsesquioxane / hexylsilsesquioxane complex (Gly-SiO 1.5 A transparent solid was obtained with the ratio (Hex=9:1).
[0141] The resulting silsesquioxane / hexylsilsesquioxane complex (Gly-SiO 1.5 Solubility tests were conducted on the compound (Hex=9:1), and it was confirmed to be soluble in highly polar solvents such as water, methanol, DMF, and DMSO.
[0142] [Manufacturing of silsesquioxane-based inorganic-organic hybrid materials] The resulting silsesquioxane / hexylsilsesquioxane complex (Gly-SiO 1.5 For (Hex=9:1), the same procedure as in Example 11 was used to obtain a silsesquioxane-based inorganic-organic hybrid material (Gly-SiO 1.5 (Hex) n -Received a BA.
[0143] <Example 15> [Silsesquioxane / Hexylsilsesquioxane / Silica complex (Gly-SiO 1.5 [Manufacturing of Hex / SiO2] Gly-TES was synthesized in the same manner as in Example 1.
[0144] Next, 5.40 mL of methanol was added, and while stirring, 0.621 g (2.5 mmol) of hexyltriethoxysilane, 2.08 g (10.0 mmol) of tetraethoxysilane, and 0.328 mL of 3.2 wt% HFaq. were slowly added dropwise, and the mixture was reacted at room temperature for 2 hours. After the reaction, the solvent was removed under reduced pressure, and the mixture was dried overnight at 40°C under reduced pressure to obtain the silsesquioxane / hexylsilsesquioxane / silica complex (Gly-SiO 1.5 A transparent solid was obtained with the ratio / Hex / SiO2 = 10:4:10.
[0145] The resulting silsesquioxane / hexylsilsesquioxane / silica complex (Gly-SiO 1.5 Solubility tests were conducted on the compound (Hex / SiO2 = 10:4:10), and it was confirmed to be soluble in highly polar solvents such as water, methanol, DMF, and DMSO.
[0146] [Manufacturing of silsesquioxane-based inorganic-organic hybrid materials] The resulting silsesquioxane / hexylsilsesquioxane / silica complex (Gly-SiO 1.5 For (Hex / SiO2=10:4:10), the same procedure as in Example 13 was used to obtain a silsesquioxane-based inorganic-organic hybrid material (Gly-SiO2). 1.5 (Hex / SiO2) n -Received a BA.
[0147] <Measurement and Evaluation> The silsesquioxane-based inorganic-organic hybrid materials obtained in Examples 1-10 and Comparative Example 1 were evaluated using the following methods. The evaluation results are shown in Table 1.
[0148] [Bending strength, bending modulus of elasticity] Bending strength and bending modulus were measured using a three-point bending test. (Preparation of test samples) For each example and comparative example, a test sample was prepared by removing the solvent to a certain extent under reduced pressure from a reaction solution between a silsesquioxane-based compound and a polyfunctional compound having at least one -B(OH)2 atomic group, which is used in the manufacturing process of silsesquioxane-based inorganic-organic hybrid materials, using an evaporator, and then pouring the solution into a Teflon® mold (25 mm long x 7 mm wide x 2 mm thick) and drying it.
[0149] In the case of Comparative Example 1, it was not possible to prepare a test sample, and therefore the test could not be conducted.
[0150] (Three-point bending test) Three-point bending tests were performed on the obtained samples using a benchtop tensile and compression testing machine (product name: MCT-2150, A&D Company, Limited). Stress responses were recorded using MSAT-Lite, with a support distance of 10 mm and a measurement speed of 10 min / mm.
[0151] [Vickers hardness scale] The Vickers hardness was measured using a micro-Vickers hardness tester (product name: HM-102, Mitutoyo Corporation) with the test samples prepared for the three-point bending test described above. The measurement was performed in accordance with JIS Z 2244.
[0152] [Young's modulus] (Preparation of test samples) For each example and comparative example, a test sample was obtained by removing the solvent to a certain extent under reduced pressure from the reaction solution of a silsesquioxane-based compound and a polyfunctional compound having at least one -B(OH)2 atomic group in the manufacturing process of a silsesquioxane-based inorganic-organic hybrid material using an evaporator, and then pouring the solution into a Teflon® mold punched into a dumbbell shape (size 7, total length 35 mm, parallel section length 12 mm × width 2 mm × thickness 1.0 mm) and drying it.
[0153] (Tensile test) Tensile tests were conducted using a load measurement stand (product name: MX2-500N, IMADA Corporation). Stress response was recorded using a force gauge ZTA500 (effective gauge dimensions: length = 12 mm, width = 2 mm, thickness = 1 mm). Young's modulus was calculated from the slope of the low-strain region (0.05~0.25%) in the obtained stress-strain curve (SS curve).
[0154] [Self-repairability] Using a parallel jig with a diameter of 12 mm, a Teflon® sheet (0.1 mm thick) with a 2 mm diameter hole was sandwiched between two circular sample sheets (film thickness 1.2 mm or less). The two sample sheets were then heat-pressed together, integrating them through the 2 mm hole. After confirming that the samples had settled at around room temperature, a tensile test was performed at a speed of 10 mm / min, and the response was recorded. Immediately after fracture, the two sheets were pressed together for a predetermined time and temperature, and the tensile test was performed again to evaluate the repair performance. The repair efficiency was calculated as follows. Healing efficacy(%)=(Max strength of Healed / Max strength of Pristine)×100
[0155] Tensile tests were performed using a load measuring stand (product name: MX2-500N, Imada Corporation). Stress response was recorded using a force gauge ZTA500 (effective gauge dimensions: length = 12 mm, width = 2 mm, thickness = 1 mm). Crimping was performed at 1 MPa.
[0156] [Total content of organic components] The total organic content in silsesquioxane-based inorganic-organic hybrid materials was calculated from the weight loss rate up to 650°C measured by thermogravimetric analysis (TGA) under nitrogen. Specifically, a thermogravimetric analyzer (Thermogravimetry Analysis: TGA, Seiko Instruments Inc., Model: 6200) was used, and measurements were taken in a Pt dish under a nitrogen atmosphere, with the temperature raised to 700°C at a rate of 10°C / min.
[0157] [Transparency Assessment] The ultraviolet-visible absorption spectra of the silsesquioxane-based inorganic-organic hybrid materials prepared in Examples 2 and 7 were measured using an ultraviolet-visible spectrophotometer (product name: V-630BIO, JASCO Corporation). Three types of measurement samples were prepared by dissolving the silsesquioxane-based inorganic-organic hybrid material in distilled water: 1 wt%, 10 wt%, and 20 wt%. These were cast onto glass substrates and dried at 100°C to prepare four samples with different film thicknesses (two samples were prepared from the 1 wt% solution). The 1 wt% solution was prepared by dissolving 5 mg of silsesquioxane-based inorganic-organic hybrid material in 495 mg of water, the 10 wt% solution by dissolving 50 mg in 450 mg of water, and the 20 wt% solution by dissolving 100 mg in 400 mg of water. The thickness of the samples prepared for each example is shown in Table 2.
[0158] [Table 1]
[0159] [Table 2]
[0160] Figure 4 shows the silsesquioxane-based inorganic-organic hybrid materials (Gly-SiO) prepared in Examples 1-3. 1.5 ) n -The stress-strain curve (SS curve) of PDBA is shown. Also, Figure 5 shows the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO) prepared in Examples 4-6. 1.5 ) n - The stress-strain curve (SS curve) of BTBA is shown.
[0161] Figure 6 shows the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO) prepared in Example 3. 1.5 ) n -The evaluation results of the self-healing of PDBA are shown. Also, Figure 7 shows the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO) prepared in Example 4. 1.5 )n -The results of the evaluation of BTBA's self-repair are shown.
[0162] Figure 8 shows the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO) prepared in Example 2. 1.5 ) n -The results of the transparency evaluation of the PDBA hybrid are shown. Also, Figure 9 shows the (Gly-SiO) fabricated in Example 7. 1.5 The results of the transparency evaluation of the (SiO2)-PDBA hybrid are shown.
[0163] From Table 1, Figure 4, Figure 6, and Figure 8, silsesquioxane compounds (Gly-SiO 1.5 ) n Example 3, in which the charging ratio of 1,4-phenyldiboronic acid (DPBA) was OH:B(OH)2 = 1:0.2, showed that the resulting silsesquioxane-based inorganic-organic hybrid material exhibited high hardness and Young's modulus, as well as excellent self-healing function and transparency. Furthermore, it was confirmed that flexural strength, flexural modulus, and Vickers hardness all improved as the amount of PDBA added increased.
[0164] From the results in Table 1, Figure 5, and Figure 7, silsesquioxane compounds (Gly-SiO 1.5 ) n Example 6, in which the charging ratio of benzene 1,3,5-triylboronic acid (BTBA) was set to OH:B(OH)2 = 1:0.2, was found to produce a silsesquioxane-based inorganic-organic hybrid material with high hardness and Young's modulus, as well as excellent self-healing function and transparency.
[0165] Also, silsesquioxane compounds (Gly-SiO 1.5 ) n The Young's modulus of the silsesquioxane-based inorganic-organic hybrid material consisting of benzene 1,3,5-triylboronic acid (BTBA) is as follows: silsesquioxane particles (Gly-SiO 1.5 ) n The Young's modulus was higher than that of a silsesquioxane-based inorganic-organic hybrid material consisting of 1,4-phenylenediboronic acid (PDBA).
[0166] Figure 10 shows the silsesquioxane-based inorganic-organic hybrid materials (Gly-SiO) prepared in Examples 1, 7, and 8. 1.5 The stress-strain curve (SS curve) of (Gly-SiO2)-PDBA is shown. Figure 11 shows the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO2) prepared in Example 7. 1.5 The results of the evaluation of the self-healing properties of (SiO2)-PDBA are shown.
[0167] From the results in Table 1 and Figure 6, it is determined that the silsesquioxane / silica composite is (Gly-SiO 1.5 Example 7, in which the charging ratio of (SiO2=8:2) and 1,4-phenylenediboronic acid (PDBA) was 1:0.12 (OH:B(OH)2=1:0.06), showed that the resulting silsesquioxane-based inorganic-organic hybrid material had high hardness and Young's modulus, as well as excellent self-healing function and transparency. The silsesquioxane-based inorganic-organic hybrid material of Example 7 is a silsesquioxane-based compound (Gly-SiO2). 1.5 ) n The hardness and Young's modulus were higher than those of the silsesquioxane-based inorganic-organic hybrid material of Example 1, which consisted of 1,4-phenylenediboronic acid (PDBA).
[0168] Figure 12 shows the silsesquioxane-based inorganic-organic hybrid materials (Gly-SiO) prepared in Examples 2, 3, 9, and 10. 1.5 ) n The stress-strain curve (SS curve) of PDBA-ZnCl2 is shown.
[0169] Examples 9 and 10, in which zinc chloride that coordinates with the tertiary amino group (an organic moiety) was added, were compared with Examples 2 and 3, in which zinc chloride was not added. The results showed that the flexural modulus improved in the examples in which zinc chloride was added. Comparing Example 2 with Example 9, the Vickers hardness also improved in Example 9, suggesting that the addition of a metal salt that forms a coordination bond with the tertiary amino group improved the strength.
[0170] Figure 13 shows the silsesquioxane-based inorganic-organic hybrid materials (Gly-SiO) prepared in Examples 11-13. 1.5 ) n -BA and (Gly-SiO 1.5 ( / SiO2) n -BA(Gly-SiO 1.5 ) n The stress-strain curve (SS curve) of PDBA-ZnCl2 is shown.
[0171] From the results in Table 1 and Figure 13, it is determined that the silsesquioxane / silica composite is (Gly-SiO 1.5 In Example 13, where the charging ratio of (SiO2 = 8:2) and boric acid (BA) was 1:0.3 (OH:B(OH)2 = 1:0.1125), the resulting silsesquioxane-based inorganic-organic hybrid material showed a high flexural modulus.
[0172] Figure 14 shows the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO) prepared in Example 14. 1.5 (Hex) n -The stress-strain curve (SS curve) of BA is shown.
[0173] From the results in Figure 14, the silsesquioxane / hexylsilsesquioxane complex (Gly-SiO 1.5 Example 14, in which the mixing ratio of (Hex=9:1) and boric acid (BA) was 1:0.225, showed that the resulting silsesquioxane-based inorganic-organic hybrid material exhibited a high flexural modulus.
[0174] Figure 15 shows the silsesquioxane-based inorganic-organic hybrid material (Gly-SiO) prepared in Example 15. 1.5 (Hex / SiO2) n -The stress-strain curve (SS curve) of BA is shown.
[0175] From the results in Figure 15, the silsesquioxane / hexylsilsesquioxane / silica complex (Gly-SiO 1.5In Example 15, where the mixing ratio of (Hex / SiO2 = 10:4:10) and boric acid (BA) was 1:0.1125, similar to Example 13, the resulting silsesquioxane-based inorganic-organic hybrid material exhibited a high flexural modulus. [Explanation of Symbols]
[0176] 1. Hydroxyl group 10 Silsesquioxane compounds 20 Polyfunctional compounds having at least one -B(OH)2 group 30 Silsesquioxane-based inorganic-organic hybrid materials
Claims
1. A silsesquioxane compound having multiple hydroxyl groups and at least one -B(OH) 2 A polyfunctional compound having an atomic group has a boronic acid ester bond formed by reacting it with, The hydroxyl group and the -B(OH) 2 The ratio to the atomic group is 0.01 to less than 0.5 -B(OH) groups per hydroxyl group. 2 The range of an atomic group, Silsesquioxane-based inorganic-organic hybrid material.
2. The silsesquioxane-based inorganic-organic hybrid material according to claim 1, wherein the boronic acid ester bond undergoes a reversible reaction, thereby having a reversible network structure.
3. The silsesquioxane-based inorganic-organic hybrid material according to claim 1, wherein the silsesquioxane-based compound is represented by the following chemical formula (1) and is surface-modified with the functional group having a hydroxyl group. (R 1 SiO 1.5 ) n (1) (In chemical formula (1), R 1 (These may be the same or different hydrocarbon groups, having 1 to 4 hydroxyl groups and containing at least one selected from the group consisting of a tertiary amino group, an ester bond, and a thioether bond, where n is an integer from 3 to 30.)
4. The silsesquioxane-based inorganic-organic hybrid material according to claim 1, wherein the silsesquioxane-based compound is a particle with an average primary particle diameter of 1 nm or more and 20 nm.
5. The silsesquioxane-based inorganic-organic hybrid material according to claim 1, wherein the silsesquioxane-based compound is a composite with silica or titanium oxide.
6. The aforementioned at least one -B(OH) 2 The polyfunctional compound having an atomic group has a functional group that reacts with a hydroxyl group, according to claim 1, the silsesquioxane-based inorganic-organic hybrid material.
7. said at least one -B(OH) 2 The silsesquioxane-based inorganic-organic hybrid material according to claim 1, wherein the polyfunctional compound having an atomic group is tetraoxysilane and / or a compound obtained by substituting one of the four ethoxy groups of tetraoxysilane with an alkyl group having 12 or less carbon atoms.
8. The silsesquioxane-based inorganic-organic hybrid material according to claim 7, wherein the alkoxy group chain of a compound obtained by substituting one of the four ethoxy groups of the tetraalkoxysilane and / or the tetraoxysilane with an alkyl group having 12 or fewer carbon atoms contains at least one of an epoxy group, a thiol group, a (meth)acrylate group, and an ether group.
9. A self-healing composition comprising a silsesquioxane-based inorganic-organic hybrid material according to any one of claims 1 to 8.
10. A self-healing molded article comprising a silsesquioxane-based inorganic-organic hybrid material according to any one of claims 1 to 8.
11. A self-healing film comprising a silsesquioxane-based inorganic-organic hybrid material according to any one of claims 1 to 8.
12. A silsesquioxane compound having multiple hydroxyl groups and at least one -B(OH) 2 A method for producing a silsesquioxane-based inorganic-organic hybrid material, comprising reacting a polyfunctional compound having an atomic group with an atom to form a boronic acid ester bond.
13. The method for producing a silsesquioxane-based inorganic-organic hybrid material according to claim 12, wherein the silsesquioxane-based compound is a composite with silica or titanium oxide.
14. The aforementioned at least one -B(OH) 2 A method for producing a silsesquioxane-based inorganic-organic hybrid material according to claim 12 or 13, wherein the polyfunctional compound having an atomic group has a functional group that reacts with a hydroxyl group.
Citation Information
Patent Citations
Hifukudensen
JP1976084082A
Curable resin composition and self-repairing material
JP2020015827A
Active energy ray curable polymer composition, cured film using the same, and laminate having the cured film, as well as manufacturing method for these
JP2021107490A
Self-repairable polymer, self-repairable material, and liquid crystal film
JP2023079191A
Organic-inorganic hybrid compact, organic-inorganic hybrid dispersion and method for producing coating film of organic-inorganic hybrid
JP2023148887A